2016
DOI: 10.1016/j.jcrysgro.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface nitridation on the epitaxial growth of few-layer sp2 BN

Abstract: Boron Nitride is a promising 2D dielectric material for use in numerous electronic applications. In order to realize this potential, a process for producing atomically thin layers on microelectronics-compatible substrates is desirable. In this paper we describe an approach to epitaxially grow few-layer sp 2 BN directly on an insulating substrate, using metal-organic chemical vapor deposition (MOCVD). We also elucidate the effect of sapphire surface nitridation on the growth characteristics. We compare the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The BN thin film was grown on sapphire by metal–organic chemical vapor deposition (MOCVD) with a thickness of 1.6 nm and a root-mean-square roughness of 0.1 nm. 29,30 The relative dielectric constant of BN is about 3, which is similar to the reported value of CVD BN. 31 MOCVD BN was first transferred onto the BP–SiO 2 –Si substrate (details in Materials and Methods).…”
Section: Device Fabricationsupporting
confidence: 85%
“…The BN thin film was grown on sapphire by metal–organic chemical vapor deposition (MOCVD) with a thickness of 1.6 nm and a root-mean-square roughness of 0.1 nm. 29,30 The relative dielectric constant of BN is about 3, which is similar to the reported value of CVD BN. 31 MOCVD BN was first transferred onto the BP–SiO 2 –Si substrate (details in Materials and Methods).…”
Section: Device Fabricationsupporting
confidence: 85%
“…The use of a buffer layer can improve the crystal quality of BN film. Smooth and high-quality h-BN films have been reported on a sapphire substrate that contained an AlO x N y buffer layer [81]. Phuong Vuong et al [82] prepared an h-BN film on the different kinds of sapphire.…”
Section: Nonmetallic Substratesmentioning
confidence: 99%
“…This morphological change can be directly correlated to the heavy Mg doping. Previous studies have shown that insufficient NH 3 flow or a parasitic reaction between the precursors may lead to grain formation, which is BN in the disordered phase (turbostratic/amorphous) [24][25][26][27]. At high Cp2Mg flow, Mg may block nitrogen atoms, leading to a low number of active N atoms in the growth front, resulting in stacking fault-induced variations in strain, which then generate a higher density of misoriented BN grains in sample D. The crystalline characteristics of the as-grown samples were studied with HR-XRD 2θ-ω scan measurements as shown in Figure 2.…”
Section: Morphology and Structural Characterizations Of Undoped And Mg Doped H-bn Layersmentioning
confidence: 99%